2012
DOI: 10.1097/wtf.0b013e32835179b1
|View full text |Cite
|
Sign up to set email alerts
|

Participatory evaluation of psychosocial interventions for children

Abstract: In the past decade, evidence-based practice has led to a more critical approach towards professional practice in the humanitarian working ¢eld. Many agencies have increased their capacity and resources to research intervention e¡ectiveness and programme impact.When evaluating psychosocial interventions, practitioners and researchers are often not only interested in intervention outcomes, but also in the external factors that in£uence e¡ectiveness, the intervention process and the views of its bene¢ciaries. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Of the 643 potentially relevant publications screened in full text, 125 were identified as eligible for this review. The grey literature search identified another 25 eligible publications, and a further seven were identified through reference list of previous reviews, with a total of 157 publications finally included in the review 24–154Table 1. summarises the characteristics of all included publications.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 643 potentially relevant publications screened in full text, 125 were identified as eligible for this review. The grey literature search identified another 25 eligible publications, and a further seven were identified through reference list of previous reviews, with a total of 157 publications finally included in the review 24–154Table 1. summarises the characteristics of all included publications.…”
Section: Resultsmentioning
confidence: 99%
“…Female non-abducted greatest improvement and male non-abducted had a negative impact. d = 1.06 (female non-abduction) d = −0.02 (male non-abduction) 2 = high 3 = low 4 = low 5 = high 6 = unclear 7 = low Claessens (2012) [ 30 ], Uganda 10–15, not stated, N = 510 Level 2, well-being Group sessions for 17 weeks delivered by non-specialist (social worker) 3 1 = high T = social worker 1 day S = not stated Intervention specifically for conflict-affected areas but adaptations not stated Instruments used not clinical, mixed-methods approach PO = well-being C = school-based recreational and connectivity exercises R = 54.3 % children achieved their goal. Themed quiz children got 87 % answers correct.…”
Section: Resultsmentioning
confidence: 99%
“…All publications reported positive promotion, prevention, and treatment effects on a range of indicators. Eighteen studies (78 %) reported positive effects on their primary outcomes [ 16 , 18 , 22 ••, 23 ••, 25 ••, 26 - 35 , 36 ••, 37 , 38 ], and eight (44 %) of these 18 showed positive impacts on specific subgroups [ 16 , 18 , 26 - 28 , 30 , 31 , 36 ••]. Therefore, only ten publications (43 %) reported positive overall promotion, prevention, and treatment effects on symptom reduction and improved well-being for their primary outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with the sixth volume (Van der Veer, 2008), there were increasing calls for establishing an evidence base for MHPSS, a ¢eld that has often been critiqued for their lack of rigorous evaluation of e¡ectiveness (Cardozo, 2008). Such tools often use participatory methods to identify appropriate approaches in psychosocial intervention, within a wide range of populations, such as war a¡ected children in Sri Lanka (Hart et al, 2007), former child soldiers in Sierra Leone and Nepal (Karki et al, 2009), war a¡ected mothers in Liberia, Sierra Leone and Uganda (McKay et al, 2011), and children in Uganda (Claessens et al, 2012). Such tools often use participatory methods to identify appropriate approaches in psychosocial intervention, within a wide range of populations, such as war a¡ected children in Sri Lanka (Hart et al, 2007), former child soldiers in Sierra Leone and Nepal (Karki et al, 2009), war a¡ected mothers in Liberia, Sierra Leone and Uganda (McKay et al, 2011), and children in Uganda (Claessens et al, 2012).…”
Section: Finding Out What Work: How Do We Monitormentioning
confidence: 99%